Realism - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Google-Books-ID: sPMBb1Ql_9UC
Keywords: Literary Criticism / American / General; Literary Criticism / General

My Contraband (1863) - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Google-Books-ID: sPMBb1Ql_9UC
Keywords: Literary Criticism / American / General; Literary Criticism / General

James Family - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Google-Books-ID: sPMBb1Ql_9UC
Keywords: Literary Criticism / American / General; Literary Criticism / General

Henry Ward Beecher - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Google-Books-ID: sPMBb1Ql_9UC
Keywords: Literary Criticism / American / General; Literary Criticism / General

John Brown - Petrie, Paul R. (The Louisa May Alcott Encyclopedia, 2001)
Louisa May Alcott (1832-1888) is arguably the most widely read 19th-century author in America. Even through the 1990s, her books continued to appear on bestseller lists and her works were made into films. She has long been a staple of children's literature courses and now also receives significant attention in American studies and women's studies classes. While her tremendous popularity has yielded numerous biographies and a growing number of critical works, very few reference books have been devoted to Alcott studies and none are particularly current or complete. This book collects in a comprehensive and reliable single volume the most important facts about Alcott's life and works.This reference surveys the basic biographical details about Alcott's family and personal life. It supplies essential information on her historical and cultural contexts, including her place in the 19th century publishing milieu, various reform movements, and major historical events, such as the Civil War. It also treats her writings, both the adult and children's works, in an accurate, informative, and accessible manner. The volume includes more than 600 alphabetically arranged entries. Each entry discusses the topic's relevance to Alcott's life and current scholarship about her. Many of the entries close with brief bibliographies, and the book concludes with a list of works for further reading.
Google-Books-ID: sPMBb1Ql_9UC
Keywords: Literary Criticism / American / General; Literary Criticism / General

Walking Blues: Making Americans from Emerson to Elvis - Parrish, Timothy (University of Massachusetts Press, 2001)
"Shows how our American social, racial, and ethnic conflicts often mark the starting point for the various acts of creation through which we make and remake ourselves as Americans."–Cover.
SCSU Faculty Scholar Award
Keywords: Civilization; Intellectual life; National characteristics; American; Cultural pluralism; Parrish; Philosophy; Blues (Music); Philosophy; United States; Social aspects; United States; United States; Popular culture; United States; Pragmatism; United States; award_winner; dept.eng; faculty_collection

Poetry Does Theology: Chaucer, Grosseteste, and the Pearl-Poet - Rhodes, James Francis (University of Notre Dame Press, 2001)
SCSU Faculty Scholar Award
Keywords: Criticism and interpretation; Langland; William; 1330?-1400? Piers Plowman; Chaucer; Geoffrey; -1400. Canterbury tales; Christian poetry; English (Middle); England; Grosseteste; Robert; 1175?-1253; History; History and criticism; Theology; History and criticism; Theology in literature; English poetry; Middle Ages; 600-1500; Patience (Middle English poem); Purity (Middle English poem); Pearl (Middle English poem); Middle English; 1100-1500; award_winner; dept.eng; faculty_collection

The World's Last Night: Poems - Schilpp, Margot (Carnegie Mellon University Press, 2001)
Keywords: American poetry; Women authors; dept.eng; faculty_collection

Down of Hawk: Poems - Shipley, Vivian (Sow's Ear Press, 2001)
Keywords: dept.eng; faculty_collection

Fishing Poems. - Shipley, Vivian (Pudding House Publications, 2001)
Keywords: dept.eng; faculty_collection

Panhandler: Special Issue: Photo/Text. - Shipley, Vivian (English Dept. of the University of West Florida, 2001)
Keywords: 20th century; Literature; Modern; dept.eng; faculty_collection

Spectacle at the disco: Boogie nights, soundtrack, and the New American musical - Ritter, K. (Journal of Popular Film and Television, 2001)
In our postmodern visual culture, the idea of spectacle conjures images of excess. In defining spectatorship, we emphasize the visual, drawing physical eyewitnesses toward the spectacular moment itself and into the reification of that moment on the film screen. However, recent Hollywood cinema has challenged the notion that all spectacle must take place within the realm of the visual, as many films strive to reach spectators aurally, via their soundtracks. In particular, popular song has been used in many commercially successful films to re-create each spectator's relationship with his or her past. Films with best-selling pop soundtracks, such as The Wedding Singer and Romy and Michelle's High School Reunion, among others, have financially exploited the spectator's attention to familiar song within comedic narratives, prompting viewers to purchase collections of songs they may already own, motivated by nostalgia and pleasant rearrangements of these songs within light, entertaining narratives. In other cases, “retro” films such as 54 and The Last Days of Disco have attempted to capitalize on the popularity of musical trends, such as disco, to revisit what the “scene” meant to its patrons, as well as what disco might mean commercially to new generations. But rarely do the songs in this type of film serve as anything but collective backdrop or the means by which a filmmaker might establish setting, particularly in terms of a decade. They merely reconfigure radio programming, reorder Top 40 hits for a theatrical space. © 2001 Taylor & Francis Group, LLC.
3 citations (Crossref) [2023-10-31]
Keywords: dept.eng